Analysis of the use of genomic DNA as a universal reference in two channel DNA microarrays - Gadgil, Mugdha; Lian, W.; Gadgil, Chetan J.; Kapur, V.; Wu, WS (BMC Genomics, 2005)
Background: DNA microarray is an invaluable tool for gene expression explorations. In the two-dye microarray, fluorescence intensities of two samples, each labeled with a different dye, are compared after hybridization. To compare a large number of samples, the 'reference design' is widely used, in which all RNA samples are hybridized to a common reference. Genomic DNA is an attractive candidate for use as a universal reference, especially for bacterial systems with a low percentage of non-coding sequences. However, genomic DNA, comprising of both the sense and anti-sense strands, is unlike the single stranded cDNA usually used in microarray hybridizations. The presence of the antisense strand in the 'reference' leads to reactions between complementary labeled strands in solution and may cause the assay result to deviate from true values. Results: We have developed a mathematical model to predict the validity of using genomic DNA as a reference in the microarray assay. The model predicts that the assay can accurately estimate relative concentrations for a wide range of initial cDNA concentrations. Experimental results of DNA microarray assay using genomic DNA as a reference correlated well to those obtained by a direct hybridization between two cDNA samples. The model predicts that the initial concentrations of labeled genomic DNA strands and immobilized strands, and the hybridization time do not significantly affect the assay performance. At low values of the rate constant for hybridization between immobilized and mobile strands, the assay performance varies with the hybridization time and initial cDNA concentrations. For the case where a microarray with immobilized single strands is used, results from hybridizations using genomic DNA as a reference will correspond to true ratios under all conditions. Conclusion: Simulation using the mathematical model, and the experimental study presented here show the potential utility of microarray assays using genomic DNA as a reference. We conclude that the use of genomic DNA as reference DNA should greatly facilitate comparative transcriptome analysis.

Stochastic model for first order reaction networks - Gadgil, Chetan J.; Lee, Chang Hyeong; Othmer, Hans G. (Bulletin of Mathematical Biology, 2005)
A stochastic model for a general system of first-order reactions in which each reaction may be either a conversion reaction or a catalytic reaction is derived. The governing master equation is formulated in a manner that explicitly separates the effects of network topology from other aspects, and the evolution equations for the first two moments are derived. We find the surprising, and apparently unknown, result that the time evolution of the second moments can be represented explicitly in terms of the eigenvalues and projections of the matrix that governs the evolution of the means. The model is used to analyze the effects of network topology and the reaction type on the moments of the probability distribution. In particular, it is shown that for an open system of first-order conversion reactions, the distribution of all the system components is a Poisson distribution at steady state. Two different measures of the noise have been used previously, and it is shown that different qualitative and quantitative conclusions can result, depending on which measure is used. The effect of catalytic reactions on the variance of the system components is also analyzed, and the master equation for a coupled system of first-order reactions and diffusion is derived.

Stochastic modeling of biological reactions - Gadgil, Chetan J. (Journal of the Indian Institute of Science, 2008)
Several biological systems comprise of reaction networks where the low number of molecules makes it inappropriate to completely characterize system behavior using a continuous approach. Biological systems are also characterized by discrete states (e.g. infected, dead) that are not amenable to the use of a continuous descriptor. This review discusses the need for adopting a discrete stochastic modeling approach for analyzing biological reactions networks. Various stochastic simulation procedures and theoretical studies are presented. The challenges in the theoretical and computational analysis of discrete stochastic biological reaction networks are discussed.

Autocatalysis: a unit process of biological systems - Gadgil, Chetan J.; Kulkarni, B. D. (Chemical Engineering Progress, 2009)

Autocatalysis in biological systems - Gadgil, Chetan J.; Kulkarni, B. D. (Aiche Journal, 2009)

Comparison of feature selection and classification combinations for cancer classification using microarray data - Vijayan, V.; Bulsara, B.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2009)

Size-independent differences between the mean of discrete stochastic systems and the corresponding continuous deterministic systems - Gadgil, Chetan J. (Bulletin of Mathematical Biology, 2009)
In this paper, it is shown that for a class of reaction networks, the discrete stochastic nature of the reacting species and reactions results in qualitative and quantitative differences between the mean of exact stochastic simulations and the prediction of the corresponding deterministic system. The differences are independent of the number of molecules of each species in the system under consideration. These reaction networks are open systems of chemical reactions with no zero-order reaction rates. They are characterized by at least two stationary points, one of which is a nonzero stable point, and one unstable trivial solution (stability based on a linear stability analysis of the deterministic system). Starting from a nonzero initial condition, the deterministic system never reaches the zero stationary point due to its unstable nature. In contrast, the result presented here proves that this zero-state is a stable stationary state for the discrete stochastic system, and other finite states have zero probability of existence at large times. This result generalizes previous theoretical studies and simulations of specific systems and provides a theoretical basis for analyzing a class of systems that exhibit such inconsistent behavior. This result has implications in the simulation of infection, apoptosis, and population kinetics, as it can be shown that for certain models the stochastic simulations will always yield different predictions for the mean behavior than the deterministic simulations.
Keywords: Biochemical reaction kinetics; Continuous systems; Deterministic chemical kinetics; Discrete systems; Stochastic reaction kinetics

Kinetic model of TBP auto-regulation exhibits bistability - Gokhale, Sucheta A.; Roshan, Reema; Khetan, Vivek; Pillai, Beena; Gadgil, Chetan J. (Biology Direct, 2010)
Background: TATA Binding Protein (TBP) is required for transcription initiation by all three eukaryotic RNA polymerases. It participates in transcriptional initiation at the majority of eukaryotic gene promoters, either by direct association to the TATA box upstream of the transcription start site or by indirectly localizing to the promoter through other proteins. TBP exists in solution in a dimeric form but binds to DNA as a monomer. Here, we present the first mathematical model for auto-catalytic TBP expression and use it to study the role of dimerization in maintaining the steady state TBP level. Results: We show that the autogenous regulation of TBP results in a system that is capable of exhibiting three steady states: an unstable low TBP state, one stable state corresponding to a physiological TBP concentration, and another stable steady state corresponding to unviable cells where no TBP is expressed. Our model predicts that a basal level of TBP is required to establish the transcription of the TBP gene, and hence for cell viability. It also predicts that, for the condition corresponding to a typical mammalian cell, the high-TBP state and cell viability is sensitive to variation in DNA binding strength. We use the model to explore the effect of the dimer in buffering the response to changes in TBP levels, and show that for some physiological conditions the dimer is not important in buffering against perturbations. Conclusions: Results on the necessity of a minimum basal TBP level support the in vivo observations that TBP is maternally inherited, providing the small amount of TBP required to establish its ubiquitous expression. The model shows that the system is sensitive to variations in parameters indicating that it is vulnerable to mutations in TBP. A reduction in TBP-DNA binding constant can lead the system to a regime where the unviable state is the only steady state. Contrary to the current hypotheses, we show that under some physiological conditions the dimer is not very important in restoring the system to steady state. This model demonstrates the use of mathematical modelling to investigate system behaviour and generate hypotheses governing the dynamics of such nonlinear biological systems.

Robustness of the drosophila segment polarity network to transient perturbations - Subramanian, K.; Gadgil, Chetan J. (IET Systems Biology, 2010)
Continuous and Boolean models for the Drosophila segment polarity network have shown that the system is able to maintain the wild-type pattern when subjected to sustained changes in the interaction parameters and initial conditions. Embryo development is likely to occur under fluctuating environmental conditions. Here, a well-established Boolean model is used to explore the ability of the segment polarity network to resist transient changes. Paths along which alternate unviable states are reached, and hence critical nodes whose state changes lead the system away from the wild-type state, are identified. It is found that the system appears to be more sensitive to changes that involve activation of normally inactive nodes. Through a simulation of the heat shock response, it is shown how a localised perturbation in one parasegment is more deleterious than a global perturbation affecting all parasegments. The sequence of events involved in the recovery of the system from a global transient heat shock condition is identified. Finally, these results are discussed in terms of the robustness of the system response.

Systems view of the protein expression process - Gokhale, Sucheta A.; Nyayanit, Dimpal; Gadgil, Chetan J. (Systems and Synthetic Biology, 2011)
Many biological processes are regulated by changing the concentration and activity of proteins. The presence of a protein at a given subcellular location at a given time with a certain conformation is the result of an apparently sequential process. The rate of protein formation is influenced by chromatin state, and the rates of transcription, translation, and degradation. There is an exquisite control system where each stage of the process is controlled both by seemingly unregulated proteins as well as through feedbacks mediated by RNA and protein products. Here we review the biological facts and mathematical models for each stage of the protein production process. We conclude that advances in experimental techniques leading to a detailed description of the process have not been matched by mathematical models that represent the details of the process and facilitate analysis. Such an exercise is the first step towards development of a framework for a systems biology analysis of the protein production process.

Analysis of miRNA regulation suggests an explanation for `unexpected' increase in target protein levels - Gokhale, Sucheta A.; Gadgil, Chetan J. (Molecular Biosystems, 2012)
MicroRNA (miRNA) has been mostly associated with decrease in target protein expression levels. Recently, `unexpected' observations of increase in target protein expression attributed to microRNA regulation have been reported. We formulate a comprehensive model for regulation by miRNA that includes both reversible mRNA-miRNA binding and selective return of RNA. We use this mathematical model incorporating multiple individual steps in the regulation process to study the simultaneous effects of these steps on the target protein level. We show that four dimensionless numbers obtained from 12 rate constants are sufficient to define the relative change in steady state target protein levels. We quantify the range of these numbers for which such pleiotropic increase in protein levels is possible, and interpret the experimental findings in the framework of our model such that the results are no longer unexpected. Finally, we show through stochastic simulation that the nature of the target protein distribution remains unchanged and the relative steady state noise levels are also completely defined by the values of these dimensionless numbers, irrespective of the individual reaction rate constants.

Mathematical model identifies conditions for 'unexpected' increase in target protein levels due to miRNA regulation - Gokhale, S.; Gadgil, Chetan J. (Mol. BioSyst., 2012)

Novel mechanism involved in temporal regulation of skin pigmentation homeostasis - Ganju, Parul; Natarajan, V. T.; Singh, A.; Vijayan, V.; Dani, Prachi P.; Kar, H. K.; Natarajan, K.; Gadgil, Chetan J.; Rani, R.; Gokhale, R. S. (Journal of Investigative Dermatology, 2012)

Simple method for incorporating dynamic effects of intronic miRNA mediated regulation - Gokhale, Sucheta A.; Hariharan, Manoj; Brahmachari, Samir K.; Gadgil, Chetan J. (Molecular Biosystems, 2012)
The importance of microRNA (miRNA) in modulating gene expression at the post-transcriptional level is well known. Such regulation has been shown to influence the dynamics of several regulatory networks including the cell cycle. In this study we incorporated regulatory effects of intronic miRNA into an existing mathematical model of the cell cycle through the use of an existing `proxy' protein - the host protein. It was observed that the incorporation of intronic miRNA mediated regulation improved the performance of the model resulting in a closer match to experimental results. To test the universality of this approach we compared the effects of intronic miRNA mediated regulation and host protein mediated regulation. Further, we compared miRNA mediated and protein mediated positive and negative feedback regulations of the target protein. We found that the target protein profiles were predominantly similar. These observations show the applicability of our method for incorporating intronic miRNA mediated dynamic effects in models for regulation of gene expression.

Comparison of methods for identifying periodically varying genes - Vijayan, V.; Deshpande, P.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2013)

IFN-gamma signaling maintains skin pigmentation homeostasis through regulation of melanosome maturation - Natarajan, Vivek T.; Ganju, Parul; Singh, Archana; Vijayan, Vinaya; Kirty, Kritika; Yadav, Shalini; Puntambekar, Shraddha; Bajaj, Sonali; Dani, Prachi P.; Kar, Hemanta K.; Gadgil, Chetan J.; Natarajan, Krishnamurthy; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Cellular homeostasis is an outcome of complex interacting processes with nonlinear feedbacks that can span distinct spatial and temporal dimensions. Skin tanning is one such dynamic response that maintains genome integrity of epidermal cells. Although pathways underlying hyperpigmentation cascade are recognized, negative feedback regulatory loops that can dampen the activated melanogenesis process are not completely understood. In this study, we delineate a regulatory role of IFN-gamma in skin pigmentation biology. We show that IFN-gamma signaling impedes maturation of the key organelle melanosome by concerted regulation of several pigmentation genes. Withdrawal of IFN-gamma signal spontaneously restores normal cellular programming. This effect in melanocytes is mediated by IFN regulatory factor-1 and is not dependent on the central regulator microphthalmia-associated transcription factor. Chronic IFN-gamma signaling shows a clear hypopigmentation phenotype in both mouse and human skin. Interestingly, IFN-gamma KO mice display a delayed recovery response to restore basal state of epidermal pigmentation after UV-induced tanning. Together, our studies delineate a new spatiotemporal role of the IFN-gamma signaling network in skin pigmentation homeostasis, which could have implications in various cutaneous depigmentary and malignant disorders.
Keywords: detanning; gene regulation; interferon; melanin

Non-coding RNA interact to regulate neuronal development and function - Iyengar, Bharat R.; Choudhary, Ashwani; Sarangdhar, Mayuresh A.; Venkatesh, K. V.; Gadgil, Chetan J.; Pillai, Beena (Frontiers in Cellular Neuroscience, 2014)
The human brain is one of the most complex biological systems, and the cognitive abilities have greatly expanded compared to invertebrates without much expansion in the number of protein coding genes. This suggests that gene regulation plays a very important role in the development and function of nervous system, by acting at multiple levels such as transcription and translation. In this article we discuss the regulatory roles of three classes of non-protein coding RNAs (ncRNAs)-microRNAs (miRNAs), piwi-interacting RNA (piRNAs) and long-non-coding RNA (lncRNA), in the process of neurogenesis and nervous function including control of synaptic plasticity and potential roles in neurodegenerative diseases. miRNAs are involved in diverse processes including neurogenesis where they channelize the cellular physiology toward neuronal differentiation. miRNAs can also indirectly influence neurogenesis by regulating the proliferation and self renewal of neural stem cells and are dysregulated in several neurodegenerative diseases. miRNAs are also known to regulate synaptic plasticity and are usually found to be co-expressed with their targets. The dynamics of gene regulation is thus dependent on the local architecture of the gene regulatory network (GRN) around the miRNA and its targets. piRNAs had been classically known to regulate transposons in the germ cells. However, piRNAs have been, recently, found to be expressed in the brain and possibly function by imparting epigenetic changes by DNA methylation. piRNAs are known to be maternally inherited and we assume that they may play a role in early development. We also explore the possible function of piRNAs in regulating the expansion of transposons in the brain. Brain is known to express several lncRNA but functional roles in brain development are attributed to a few lncRNA while functions of most of the them remain unknown. We review the roles of some known lncRNA and explore the other possible functions of lncRNAs including their interaction with miRNAs.
Keywords: gene expression regulation; lncRNA; miRNA; network-motifs; piRNA

Mathematical modeling of combinatorial regulation suggests that apparent positive regulation of targets by miRNA could be an artifact resulting from competition for mRNA - Nyayanit, Dimpal; Gadgil, Chetan J. (RNA-A Publication of the RNA Society, 2015)
MicroRNAs bind to and regulate the abundance and activity of target messenger RNA through sequestration, enhanced degradation, and suppression of translation. Although miRNA have a predominantly negative effect on the target protein concentration, several reports have demonstrated a positive effect of miRNA, i.e., increase in target protein concentration on miRNA overexpression and decrease in target concentration on miRNA repression. miRNA-target pair-specific effects such as protection of mRNA degradation owing to miRNA binding can explain some of these effects. However, considering such pairs in isolation might be an oversimplification of the RNA biology, as it is known that one miRNA interacts with several targets, and conversely target mRNA are subject to regulation by several miRNAs. We formulate a mathematical model of this combinatorial regulation of targets by multiple miRNA. Through mathematical analysis and numerical simulations of this model, we show that miRNA that individually have a negative effect on their targets may exhibit an apparently positive net effect when the concentration of one miRNA is experimentally perturbed by repression/overexpression in such a multi-miRNA multitarget situation. We show that this apparent unexpected effect is due to competition and will not be observed when miRNA interact noncompetitively with the target mRNA. This result suggests that some of the observed unusual positive effects of miRNA may be due to the combinatorial complexity of the system rather than due to any inherently unusual positive effect of the miRNA on its target.
Keywords: combinatorial binding; mathematical model; miRNA; post-transcriptional regulation

Ranking of reactions based on sensitivity of protein noise depends on the choice of noise measure - Gokhale, Sucheta A.; Gadgil, Chetan J. (Plos One, 2015)
Gene expression is a stochastic process. Identification of the step maximally affecting noise in the protein level is an important aspect of investigation of gene product distribution. There are numerous experimental and theoretical studies that seek to identify this important step. However, these studies have used two different measures of noise, viz. coefficient of variation and Fano factor, and have compared different processes leading to contradictory observations regarding the important step. In this study, we performed systematic global and local sensitivity analysis on two models of gene expression to investigate relative contribution of reaction rate parameters to steady state noise in the protein level using both the measures of noise. We analytically and computationally showed that the ranking of parameters based on the sensitivity of the noise to variation in a given parameter is a strong function of the choice of the noise measure. If the Fano factor is used as the noise measure, translation is the important step whereas for coefficient of variation, transcription is the important step. We derived an analytical expression for local sensitivity and used it to explain the distinct contributions of each reaction parameter to the two measures of noise. We extended the analysis to a generic linear catalysis reaction system and observed that the reaction network topology was an important factor influencing the local sensitivity of the two measures of noise. Our study suggested that, for the analysis of contributions of reactions to the noise, consideration of both the measures of noise is important.

Identification of unintuitive features of sumoylation through mathematical modeling - Puntambekar, Shraddha S.; Nyayanit, Dimpal; Saxena, Priyanka; Gadgil, Chetan J. (Journal of Biological Chemistry, 2016)
Sumoylation is a multistep, multienzymatic post-translational modification in which a small ubiquitin-like modifier protein (SUMO) is attached to the target. We present the first mathematical model for sumoylation including enzyme mechanism details such as autosumoylation of E2 and multifunctional nature of SENP. Simulations and analysis reveal three nonobvious properties for the long term response, modeled as an open system: (i) the steady state sumoylation level is robust to variation in several enzyme properties; (ii) even when autosumoylation of E2 results in equal or higher activity, the target sumoylation levels are lower; and (iii) there is an optimal SENP concentration at which steady state target sumoylation level is maximum. These results are qualitatively different for a short term response modeled as a closed system, where e.g. sumoylation always decreases with increasing SENP levels. Simulations with multiple targets suggest that the available SUMO is limiting, indicating a possible explanation for the experimentally observed low fractional sumoylation. We predict qualitative differences in system responses at short post-translational and longer transcriptional time scales. We thus use this mechanism-based model to explain system properties and generate testable hypotheses for existence and mechanism of unexpected responses.

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.

Systematic comparison of the response properties of protein and RNA mediated gene regulatory motifs - Iyengar, Bharat Ravi; Pillai, Beena; Venkatesh, K. V.; Gadgil, Chetan J. (Molecular BioSystems, 2017)
We present a framework enabling the dissection of the effects of motif structure (feedback or feedforward), the nature of the controller (RNA or protein), and the regulation mode (transcriptional, post-transcriptional or translational) on the response to a step change in the input. We have used a common model framework for gene expression where both motif structures have an activating input and repressing regulator, with the same set of parameters, to enable a comparison of the responses. We studied the global sensitivity of the system properties, such as steady-state gain, overshoot, peak time, and peak duration, to parameters. We find that, in all motifs, overshoot correlated negatively whereas peak duration varied concavely with peak time. Differences in the other system properties were found to be mainly dependent on the nature of the controller rather than the motif structure. Protein mediated motifs showed a higher degree of adaptation i.e. a tendency to return to baseline levels; in particular, feedforward motifs exhibited perfect adaptation. RNA mediated motifs had a mild regulatory effect; they also exhibited a lower peaking tendency and mean overshoot. Protein mediated feedforward motifs showed higher overshoot and lower peak time compared to the corresponding feedback motifs.

Method for identification of sensitive nodes in boolean models of biological networks - Dnyane, Pooja A.; Puntambekar, Shraddha S.; Gadgil, Chetan J. (IET Systems Biology, 2018)
Biological systems are often represented as Boolean networks and analysed to identify sensitive nodes which on perturbation disproportionately change a predefined output. There exist different kinds of perturbation methods: perturbation of function, perturbation of state and perturbation in update scheme. Nodes may have defects in interpretation of the inputs from other nodes and calculation of the node output. To simulate these defects and systematically assess their effect on the system output, two new function perturbations, referred to as not of function' and function of not', are introduced. In the former, the inputs are assumed to be correctly interpreted but the output of the update rule is perturbed; and in the latter, each input is perturbed but the correct update rule is applied. These and previously used perturbation methods were applied to two existing Boolean models, namely the human melanogenesis signalling network and the fly segment polarity network. Through mathematical simulations, it was found that these methods successfully identified nodes earlier found to be sensitive using other methods, and were also able to identify sensitive nodes which were previously unreported.
Keywords: biological networks; Boolean functions; Boolean models; fly segment polarity network; human melanogenesis signalling network; perturbation methods; Perturbation theory; physiological models

Mathematical model of the multi-amino acid multi-transporter system predicts uptake flux in CHO cells - Sreejan, Ashley; Gadgil, Mugdha; Gadgil, Chetan J. (Journal of Biotechnology, 2022)
Supply and uptake of amino acids is of great importance to mammalian cell culture processes. Mammalian cells such as Chinese hamster ovary (CHO) cells express several amino acid (AA) transporters including uniporters and exchangers. Each transporter transports multiple AAs, making prediction of the effect of changed medium composition or transporter levels on individual AA transport rate challenging. A general kinetic model for such combinatorial amino acid transport, and a simplified analytical expression for the uptake rate as a function of amino acid concentrations and transporter levels is presented. From this general model, a CHO cell-specific AA transport model, to our knowledge the first such network model for any cell type, is constructed. The model is validated by its prediction of reported uptake flux and dependencies from experiments that were not used in model construction or parameter estimation. The model defines theoretical conditions for synergistic/repressive effect on the uptake rates of other AAs upon external addition of one AA. The ability of the CHO-specific model to predict amino acid interdependencies experimentally observed in other mammalian cell types suggests its robustness. This model will help formulate testable hypotheses of the effect of process changes on AA initial uptake, and serve as the AA transport component of kinetic models for cellular metabolism.
Keywords: Amino acid transport; CHO cell; Exchanger; mathematical model; Multiple transporters

SUMOylation of dorsal attenuates Toll/NF-kappa B signaling - Hegde, Sushmitha; Sreejan, Ashley; Gadgil, Chetan J.; Ratnaparkhi, Girish S. (Genetics, 2022)
In Drosophila, Toll/NF-kappa B signaling plays key roles in both animal development and in host defense. The activation, intensity, and kinetics of Toll signaling are regulated by posttranslational modifications such as phosphorylation, SUMOylation, or ubiquitination that target multiple proteins in the Toll/NF-kappa B cascade. Here, we have generated a CRISPR-Cas9 edited Dorsal (DL) variant that is SUMO conjugation resistant. Intriguingly, embryos laid by dl(SCR) mothers overcome dl haploinsufficiency and complete the developmental program. This ability appears to be a result of higher transcriptional activation by DLSCR. In contrast, SUMOylation dampens DL transcriptional activation, ultimately conferring robustness to the dorso-ventral program. In the larval immune response, dl(SCR) animals show an increase in crystal cell numbers, stronger activation of humoral defense genes, and high cactus levels. A mathematical model that evaluates the contribution of the small fraction of SUMOylated DL (1-5%) suggests that it acts to block transcriptional activation, which is driven primarily by DL that is not SUMO conjugated. Our findings define SUMO conjugation as an important regulator of the Toll signaling cascade, in both development and host defense. Our results broadly suggest that SUMO attenuates DL at the level of transcriptional activation. Furthermore, we hypothesize that SUMO conjugation of DL may be part of a Ubc9-dependent mechanism that restrains Toll/NF-kappa B signaling.
Keywords: Drosophila; haploinsufficiency; innate immunity; SUMO; transcription

Physiologically-based pharmacokinetic model for tuberculosis drug disposition at extrapulmonary sites - Ramachandran, Aparna; Gadgil, Chetan J. (CPT-Pharmacometrics & Systems Pharmacology, 2023)
Tuberculosis (TB) is a leading cause of mortality attributed to an infectious agent. TB primarily targets the lungs, but in about 16% cases can affect other organs as well, giving rise to extrapulmonary TB (EPTB). However, an optimal regimen for EPTB treatment is not defined. Although the recommended treatment for most forms of EPTB is the same as pulmonary TB, the pharmacokinetics of EPTB therapy are not as well studied. To address this gap, we formulate a whole-body physiologically-based pharmacokinetic (PBPK) model for EPTB that for the first time includes the ability to simulate drug concentrations in the pleura and lymph node, the most commonly affected sites of EPTB. Using this model, we estimate the time-dependent concentrations, at potential EPTB infection sites, of the following four first-line anti-TB drugs: rifampicin, ethambutol, isoniazid, and pyrazinamide. We use reported plasma concentration kinetics data to estimate model parameters for each drug and validate our model using reported concentration data not used for model formulation or parameter estimation. Model predictions match the validation data, and reported pharmacokinetic parameters (maximum plasma concentration, time to reach maximum concentration) for the drugs. The model also predicts ethambutol, isoniazid, and pyrazinamide concentrations in the pleura that match reported experimental values from an independent study. For each drug, the predicted drug concentrations at EPTB sites are compared with their critical concentration. Simulations suggest that although rifampicin and isoniazid concentrations are greater than critical concentration values at most EPTB sites, the concentrations of ethambutol and pyrazinamide are lower than their critical concentrations at most EPTB sites.

Network motifs exhibiting a differential response to spaced and massed inputs - Sreejan, Ashley; Saxena, Priyanka; Gadgil, Chetan J. (Learning & Memory, 2024)
One characteristic of long-term memory is the existence of an inverted U-shaped response to increasing intervals between training sessions, and consequently, an optimal spacing that maximizes memory formation. Current models of this spacing effect focus on specific molecular components and their interactions. Here, we computationally study the underlying network architecture, in particular, the potential of motif dynamics in qualitatively capturing the spacing effect in a manner that is independent of the animal model, biomolecular components, and the timescales involved. We define a common training and test protocol, and computationally identify network topologies that can qualitatively replicate the experimentally observed characteristics of the spacing effect. For 41 motifs derived from fundamental network architectures such as autoregulation, feedback, and feedforward motifs, we tested their capacity to manifest the spacing effect in terms of an inverted U-shaped response curve, using different combinations of stimulation protocols, response metrics, and kinetic parameters. Our findings indicate that positive feedback motifs where the stimulus enhances conversion reaction in the loop replicate the spacing effect across all response metrics, while feedforward motifs exhibit a metric-specific spacing effect. For some parameter combinations, linear cascades of activation and conversion reactions were found sufficient to qualitatively exhibit spacing effect characteristics.

Mycobacteria-specific prodrug to overcome phenotypic AMR in mycobacterium tuberculosis - Kumar, T. Anand; Birua, Shalini; Mallojjala, Sharath Chandra; Mukherjee, Piyali; Singh, Samsher; Kaul, Grace; Ramachandran, Aparna; Akhir, Abdul; Chopra, Sidharth; Gadgil, Chetan J.; Hirschi, Jennifer S.; Singh, Amit; et al. (Journal of Medicinal Chemistry, 2025)
Most front-line tuberculosis (TB) drugs are ineffective against hypoxic nonreplicating Mycobacterium tuberculosis (Mtb), largely due to poor permeability, leading to reduced drug accumulation and target engagement. To overcome this phenotypic antimicrobial resistance (AMR), we developed nitroheteroaryl prodrugs for Moxifloxacin (MXF), a front-line TB drug. These prodrugs are activated by bacterial nitroreductases (NTR), which are overexpressed in hypoxic Mtb. NTR-mediated electron transfer and protonation facilitate rapid cleavage of the protective group, releasing active MXF. The lead prodrug exhibited comparable efficacy to MXF in replicating Mtb and significantly enhanced lethality in nonreplicating Mtb. Drug accumulation studies confirmed a modest but significant increase in MXF levels in nonreplicating Mtb treated with the prodrug, suggesting improved permeability. A mathematical model integrating growth and drug-killing kinetics further elucidated how permeability differences impact lethality. Together, these findings highlight enzyme-activated prodrugs as a promising strategy to address phenotypic AMR in Mtb